2019
DOI: 10.1111/acfi.12579
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐listings and dividend size and stability: evidence from China

Abstract: We investigate the relationship between cross‐listings and dividend policy. We find that Chinese cross‐listed firms have lower and more stable dividends than their non‐cross‐listed peers, and that dividends become more stable the longer a company has been cross‐listed. We also find the strength of the cross‐listing/dividend policy relationship varies based on the market where the shares are cross‐listed. The strength of the relationship varies from B‐shares (least strong) to Hong Kong shares (stronger) to Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
2
8
1
Order By: Relevance
“…Moreover, Lam et al (2012) confirmed for Chinese companies, that those entities that are cross-listed pay lower cash dividends than companies with state ownership. This latter outcome is in line with Cheng et al (2021) study, which confirmed that cross-listed companies from China pay lower and more stable dividends than their single-listed counterparts. Cheng et al (2021) employed also Lintner's model and obtained lower SOA coefficient (0.41) for cross-listed companies than for non-cross-listed (0.53).…”
Section: Determinants Of Dividend Policy and Smoothingsupporting
confidence: 88%
See 3 more Smart Citations
“…Moreover, Lam et al (2012) confirmed for Chinese companies, that those entities that are cross-listed pay lower cash dividends than companies with state ownership. This latter outcome is in line with Cheng et al (2021) study, which confirmed that cross-listed companies from China pay lower and more stable dividends than their single-listed counterparts. Cheng et al (2021) employed also Lintner's model and obtained lower SOA coefficient (0.41) for cross-listed companies than for non-cross-listed (0.53).…”
Section: Determinants Of Dividend Policy and Smoothingsupporting
confidence: 88%
“…The obtained results of the SOA for the DR-subsample indicate that cross-listed do not follow highly smoothed dividend policy prevalent on the more mature, foreign stock exchanges. Higher level of the SOA for the cross-listed firms' subsample stays in contrast with Cheng et al (2021) study for Chinese companies. We believe that that difference in the SOA levels is related to, first more heterogeneous research sample in our study, and second to divergent definitions of dependent variable in Lintner's equation.…”
Section: Resultscontrasting
confidence: 65%
See 2 more Smart Citations
“…Our paper selects 2,829 non‐financial A‐share listed companies in 15 industry sectors from the China securities markets over the period from 2011 to 2018. In China, only stocks traded between Chinese domestic investors are categorised as A‐shares (Cheng et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%